Effects of Carbon Ion Beam Irradiation on Butanol Tolerance and Production of Clostridium acetobutylicum - Gao, Yue; Zhang, Miaomiao; Zhou, Xiang; Guo, Xiaopeng; Lei, Cairong; Li, Wenjian; Lu, Dong (Frontiers in Microbiology, 2020)
Clostridium acetobutylicum (C. acetobutylicum) has considerable potential for use in bioenergy development. Owing to the repeated use of traditional mutagenesis methods, the strains have developed a certain tolerance. The rheology of the bioprocess and the downstream processing of the product heavily depend on the ability of C. acetobutylicum mutants to produce butanol. Carbon ion beam irradiation has advantages over traditional mutation methods for fermentative production because of its dose conformity and superb biological effectiveness. However, its effects on the specific productivity of the strains have not been clearly understood. In this study, we screened five mutants through carbon ion beam irradiation; mutant Y217 achieved a butanol-production level of 13.67 g/L, exceeding that of wild-type strain ATCC 824 (i.e.,9.77 g/L). In addition, we found that the mutant maintained normal cell membrane integrity under the stimulation of 15 g/L butanol, whereas the intracellular macromolecules of wild-type strain ATCC 824 leaked significantly. Subsequently, we used the response surface methodology (RSM) to determine if the mutant cell membrane integrity improved the butanol tolerance. We verified that with the addition of butanol, the mutant could be fermented to produce 8.35 g/L butanol, and the final butanol concentration in the fermentation broth could reach 16.15 g/L. In this study, we proved that under butanol stress, mutant Y217 features excellent butanol production and tolerance and cell membrane integrity and permeability; no prior studies have attempted to do so. This will serve as an interesting and important illustration of the complexity of genetic control of the irradiation mutation of C. acetobutylicum strains. It may also prove to be useful in the bioengineering of strains of the mutant for use in the predevelopment stage.